Utilization of Audiovisual Media to Improve Vocabulary Comprehension of Deaf Children - Mutiara Ramadhan Nasution; Deassy Yunita Siregar (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Learning English remains a challenge for students in Indonesia, especially for deaf students who rely on visual input and often face limitations in conventional teaching methods. However, studies focusing specifically on the use of audiovisual media for deaf learners are still limited. Therefore, audiovisual media are considered an effective strategy to support vocabulary development. This study aims to examine how audiovisual media improve English vocabulary comprehension among deaf students. This research employed a qualitative case study design. Data were collected through interviews, classroom observations, and documentation at a Special School (SLB) in Percut Sei Tuan, North Sumatra, involving deaf students who had studied English for one year. Data were analyzed using Braun and Clarke’s (2006) thematic analysis, and validity was ensured through data triangulation. The findings indicate that audiovisual media significantly improve students’ vocabulary comprehension, learning focus, and engagement, thus supporting inclusive educational practices.